Users’ behaviour concept on the usage of the bicycle sharing system / Nur Fadhilah Zaharin and Ahmad Nazrin Aris Anuar - Zaharin, Nur Fadhilah; Anuar, Ahmad Nazrin Aris (2018)
Bicycle sharing system is viewed as a customer-oriented concept where the behaviour of the users is a need for understanding. However, studies of such concept where are related to users' behaviour are limited thus leaving a gap of knowledge and practice in the area. Thus, this study is a concept paper that aims to determine users’ behaviour framework on the usage of bicycle sharing system. The findings of this study have identified three elements from the aspect of perceived value and also three elements from the aspect of perceived ease of use which are associated to the user's behaviour framework. This study will encourage providers to increase the services based on the behaviour of the users.